Assistance for Pokdarwis Zwageri Borneo in providing clean water needs for rural tourism areas - Dwi Ermawati Rahayu; Ika Meicahayanti; Agus Winarno; Yudi Sukmono; Desthia Pinasthika; Indah Septiliani; Intan Baiduri (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Pokdarwis "Zwageri Borneo" in Manunggal Jaya Village, Kutai Kartanegara Regency, prioritizes agricultural tourism. However, this tourism activity has been hindered by the lack of basic infrastructure. There is an adequate quantity of raw water from ex-mining ponds, but quality parameters such as turbidity, Fe, and Mn do not meet the required standards. To address this, a water treatment technology that is easy to operate and maintain—a combination of roughing filter and aeration—has been implemented. In this activity, a Water Treatment Plant (WTP) with a processing capacity of 46.3 l/minute has been constructed. Technology transfer and management assistance have been provided to Pokdarwis. Additionally, maps have been created to support tourism promotion. This initiative is expected to be sustainable with Pokdarwis independently managing the WTP facilities. Conservation of catchment areas is necessary to maintain the quantity and quality of raw water. Cross-sectoral collaboration with district and provincial tourism offices, village governments, and the private sector is essential to support Pokdarwis.